Phenolic content and antioxidant properties of selected medicinal and culinary herbs under different temperatures - Haida, Zainol; Nakasha Juju, Jaafar; Hakiman, Mansor (ScopeMed, 2020)
Medicinal and culinary herbs have been used since a long time ago in food to enhance flavor, color, aroma as well as to increase self-life. Herbs are rich in numerous bioactive compounds and possess a wide range of therapeutic properties. This study was conducted to analyze phenolic contents (total polyphenols, phenolic acids and flavonoids contents) and antioxidant activity (DPPH free radical scavenging activity) of selected medicinal and culinary herbs (oregano, basil, coriander, rosemary and thyme) as exposed to different water temperature (27 and 100ºC). From this study, the highest total polyphenols and phenolic acids contents were recorded from 100ºC oregano and thyme extracts with 3.79 and 7.06 mg GAE/g DW, respectively. Meanwhile, the highest total flavonoids content was recorded from the 100ºC oregano extract (3.12 mg QE/g DW) and the highest DPPH free radical scavenging activity was exhibited from 100ºC rosemary extract (3.72 mg TE/g DW). Hence, it is suggesting that herbs used in this study were able to withstand high temperature and suitable to use for cooking. [Fundam Appl Agric 2020; 5(2.000): 211-215]